2017
DOI: 10.1002/cnm.2918
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark problems for numerical treatment of backflow at open boundaries

Abstract: In computational fluid dynamics, incoming velocity at open boundaries, or backflow, often yields unphysical instabilities already for moderate Reynolds numbers. Several treatments to overcome these backflow instabilities have been proposed in the literature. However, these approaches have not yet been compared in detail in terms of accuracy in different physiological regimes, in particular because of the difficulty to generate stable reference solutions apart from analytical forms. In this work, we present a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 33 publications
0
53
1
Order By: Relevance
“…The jet breakdown location shifted continuously downstream of the sudden expansion and eventually reached the end of the computational domain, which caused backflow at the outlet and a diverged numerical solution. The latter is well known; however, Passerini et al still reported a lower lmax+ compared with our lmax+=11.00.1emfalse(laverage+=1.3false) obtained on the 80M linear ( P1P1) element equivalent mesh with constant node spacing. This comparison may indicate that the mesh used by Passerini et al was rather refined in the high shear rate regions, and consequently equally coarser elsewhere.…”
Section: Discussioncontrasting
confidence: 51%
“…The jet breakdown location shifted continuously downstream of the sudden expansion and eventually reached the end of the computational domain, which caused backflow at the outlet and a diverged numerical solution. The latter is well known; however, Passerini et al still reported a lower lmax+ compared with our lmax+=11.00.1emfalse(laverage+=1.3false) obtained on the 80M linear ( P1P1) element equivalent mesh with constant node spacing. This comparison may indicate that the mesh used by Passerini et al was rather refined in the high shear rate regions, and consequently equally coarser elsewhere.…”
Section: Discussioncontrasting
confidence: 51%
“…In this work as well as in most of related work, the error estimates for problem (1) usually are derived under the no-slip condition u u u = 0 0 0 for the velocity. This excludes, for example, channel-like problems with in-and outflow which are important, for example for biomedical flows (see the review [7]). Therefore, an extension of the error estimates to such more practically relevant flow problems is desired.…”
Section: Practically Relevant Boundary Conditionsmentioning
confidence: 99%
“…This indicates that when a ij (i, j = 1, 2) are chosen to be sufficiently small the matrix R will guarantee the positive semi-definiteness of the matrix Q and the non-positivity of the surface integral term in (4).…”
Section: Energy-stable Boundary Conditions Based On a Quadratic Formmentioning
confidence: 99%
“…We refer the reader to e.g. those of [2,3] which are given based on a weak formulation of the Navier-Stokes equations, and also to [4] for a recent study of several methods in the context of physiological flows. We also refer to [9,15,38] for methods dealing with two-phase and multiphase outflows and open boundaries and related issues.…”
Section: Introductionmentioning
confidence: 99%